The large Gunnera’s (G. tinctoria and G. manicata) in Europe in relation to EU regulation 1143/2014 - Johan L. C. H. van Valkenburg; Bruce A. Osborne; Marcel Westenberg (PLoS ONE, 2023)
Incorrect labelling of plants in the horticultural trade and misidentification is widespread. For the inspection services of the EU member states, correct identification of G. tinctoria has become important since the species was added to the List of Union concern in accordance with EU regulation 1143/2014 in August 2017. In the horticultural trade Gunnera plants are generally of modest dimensions and rarely flowering, so that the major distinguishing morphological characters for the identification of the two large species, G. tinctoria and G. manicata, are missing. As G. tinctoria is included in the EU regulation, its trade is prohibited, although the closely related species, G. manicata is not included on the list. Given that it is often difficult to distinguish between these two large herbaceous species using morphological attributes we used standard chloroplast DNA barcode markers, supplemented at a later stage by ITS markers. Plant material of putative G. tinctoria or G. manicata was obtained from the native and introduced range, both from “wild” sources, botanical gardens, and the horticultural trade. In western Europe plants circulating in the horticultural trade turned out to be predominantly G. tinctoria, with only one plant in cultivation identified as true G. manicata and the G. manicata found in botanical gardens was a hybrid recently described as G. x cryptica.